HUBUNGAN PERILAKU PEMELIHARAAN KESEHATAN GIGI DAN MULUT PADA PASIEN DIABETES MELITUS II - Ismaturrahmi; Reca (Jurnal Online Keperawatan Indonesia, 2024)
Background: 2018 Basic Health Research Data (Riskesdas) DM problem in Indonesia ranks second in the world, the prevalence of DM is 10.9%. Based on the results of health research in 2018, the prevalence of dental and oral health problems in Indonesia was 57.6%, an increase from the 2013 report of 31.7%. The prevalence of gingivitis in Indonesia is second, showing a figure of 96.58%. Based on the problems that researchers found, of the 10 patients suffering from diabetes mellitus who visited the PTM clinic and were examined at the dental clinic, there were 7 patients who experienced gingivitis. Objective: This study was to determine the relationship between oral health maintenance behavior and gingivitis status in type II diabetes patients at UPTD Pukesmas Krueng Barona Jaya. Method: Cross-sectional design with a sample of 30 diabetes mellitus patients who visited Pukesma Krueng Barona Jaya. Data collection was carried out through interviews using questionnaires and examination of gingivitis status with the gingival index. The research took place for 3 weeks from April to May 2024. Results: Based on statistical analysis using the Chi-Square test, it shows that there is a significant relationship between the behavior of type II diabetes mellitus sufferers and the status of dental and oral hygiene (p = 0.018). Conclusion: This research can be concluded that there is a significant relationship between dental and oral health maintenance behavior and gingival status in type II diabetes patients. Suggestion: It is hoped that patients suffering from Diabetes Mellitus will diligently control their blood sugar and the health of their teeth and mouth every 6 months and maintain the cleanliness of their teeth and mouth by brushing their teeth properly and correctly to avoid oral diseases, especially gingivitis.